Brain abscess of odontogenic origin in a man with interatrial defect - Milli, B.; Rocci, A.; Paganelli et al., E. (Acta Biomedica Atenei Parmensis, 2011)
A 65-year-old man with previous surgery for cyanotic congenital heart disease was admitted to our hospital with fever, headache and visual disturbances due to a right occipital brain abscess as shown through CT-scan. A comprehensive workup looking for a source of infection was negative except for an orthopantomogram showing multiple dental caries. A transesophageal echocardiogram (TEE) bubble study revealed the permanence of an atrial septal defect with a moderate right-to-left shunt. The culture of the abscess content showed flora commonly found in the oropharynx that responded to antimicrobial therapy. We hypothesize that the underlying mechanism is a significant bacterial load from dental infections that enters the arterial circulation through the interatrial defect. If a brain abscess is identified without any adjacent source of infection, then a transesophageal echocardiogram is indicated to exclude right to left shunt. If a shunt is found, then hematogenous spread of flora normally found in the oropharynx should be suspected. Surgical evacuation followed by antimicrobial therapy is warranted. Once the infection is eliminated, long term anticoagulation or anatomic closure of the interatrial defect with good oral hygiene could be valid strategies for preventing recurrence.